Tat’yana Sergeyevna Fyodorova (to the 75th birthday) - article Editorial (Бюллетень сибирской медицины, 2008)
The creative biography of Tat’yana Sergeyevna Fyodorova, famous native scientist, doctor of medicine, professor of Siberian State Medical University (Tomsk) is presented.